2019
DOI: 10.1042/bsr20180409
|View full text |Cite
|
Sign up to set email alerts
|

Biological enrichment prediction of polychlorinated biphenyls and novel molecular design based on 3D-QSAR/HQSAR associated with molecule docking

Abstract: Based on the experimental data of octanol-water partition coefficients (Kow, represents bioaccumulation) for 13 polychlorinated biphenyl (PCB) congeners, comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) were used to establish 3D-QSAR models, combined with the hologram quantitative structure–activity relationship (HQSAR), the substitution sites (mono-substituted and bis-substituted) and substituent groups (electron-withdrawing hydrophobic groups) that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…26 In the modeling study, we randomly divided the 43 compounds into a training set and a test set with a ratio of roughly 3 : 1, in which the training group included 33 molecules (indicated by the superscript symbol ''*'') and the test group contained 10 molecules. 27 Molecular construction and structural optimization of these compounds were executed utilizing the molecular manipulation tool SYBYL-X 2.0. Tripos force field and Powell's energy gradient method were adopted to minimize the energy of all small molecules.…”
Section: Molecular Construction and Structural Optimizationmentioning
confidence: 99%
“…26 In the modeling study, we randomly divided the 43 compounds into a training set and a test set with a ratio of roughly 3 : 1, in which the training group included 33 molecules (indicated by the superscript symbol ''*'') and the test group contained 10 molecules. 27 Molecular construction and structural optimization of these compounds were executed utilizing the molecular manipulation tool SYBYL-X 2.0. Tripos force field and Powell's energy gradient method were adopted to minimize the energy of all small molecules.…”
Section: Molecular Construction and Structural Optimizationmentioning
confidence: 99%
“…Bonefeld-Jorgensen et al [ 15 ] studied the anti-androgenic activity of 3 PCBs in Chinese hamster ovary cells through a luciferase reporter gene experiment and found that the anti-androgenic activity of PCB-153 and PCB-180 was significantly less than that of PCB-138. Although PCBs were prohibited from being produced and used worldwide in the 1970s and listed in the Stockholm Convention on Persistent Organic Pollutants [ 16 , 17 , 18 ], the risk of anti-oestrogenic activity, by a large number of PCBs remaining in the environment, still cannot be ignored. How to effectively regulate and avoid them so as to reduce the damage to human health and environmental pollution is a trending issue that needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%